Implementation level indicators of public facilities in Surabaya to smoke-free area regulation - Christanto, Daniel; Martini, Santi; Dwi Artanti, Kurnia; Indriani, Diah (Universitas Udayana, 2023)
Background and purpose: The regulation of smoke-free area in Surabaya was adopted since 2008 and amended in 2019. Hotel, restaurants, and cafes are smokefree dedicated area under the regulation. Therefore, it is very important to review the implementation level of smoke-free area regulations in public places such as hotels, restaurants and cafes. This study aims to analyze how strong the indicators that forms the implementation level of public facilities with smoke free area regulations in Surabaya. Methods: This was a cross sectional survey carried out in 88 public facilities consisting of hotels and restaurants between June-August 2021. Confirmatory Factor Analysis (CFA) was carried out with the Analysis of Moment Structures (AMOS) Application to test the strength of each smoke-free area monitoring indicators that forms the implementation level of these public facilities. These indicators include: awareness of smoke-free area regulations, smoke-free area internal promotion, installation of smoke-free signs, no colaboration with tobacco industries, no violations and owning an internal policy related to smoke-free. Results: There were three strong indicators that are strongest in shaping smoke-free area implementation level at public facilities in Surabaya, including awareness of smoke-free area regulations (CFA 4.681), smoke-free area internal promotion (CFA 2.609) and installing a smoke-free sign (CFA 1.000). Meanwhile, the other three indicators showed weak association. Conclusion: Awareness of smoke-free area regulations, smoke-free area internal promotion and installation of smoke-free sign were the strong indicators for smokefree law (SFL) implementation. It is important to push for more internal dissemination involving cross sectors and improve other indicators.